Factors that contribute to the decreasing of employees’ turnover intention in the Panasonic Energy Malaysia Sdn Bhd, Kulim Kedah / Ku Nur Sahira Ku Ishak ...[et al.] - Ku Ishak, Ku Nur Sahira; Dzaharin, Nadzirah (2018)
Turnover intention of employees is one of the critical issues especially in Manufacturing Sector. The turnover intention of employees has a negative impact on the organization if it is not been controlled. This research study was conducted at Panasonic Energy Malaysia Sdn Bhd, Kulim Kedah. However, the finding shows there is a backward trend which is downtrend in turnover rates. Thus, the research was to investigate the factors that contribute to the decreasing number of employees’ turnover intention in the Panasonic Energy Malaysia Sdn Bhd, Kulim Kedah. Questionnaire were distributed and the stratified random sampling method was used to analyze the 285 sample collected. The trends of turnover intention in the Panasonic Energy Malaysia Sdn Bhd, Kulim Kedah were analyzed by the research objectives findings that tested on four factors which are job satisfaction, working environment, monetary reward and leadership style.